Tectonic vicariance versus Messinian dispersal in western Mediterranean ground beetles. (15th July 2018) - Faille, Arnaud; Casale, Achille; Hernando, Carles; Aït Mouloud, Salah; Ribera, Ignacio
Abstract: The complex geological history of the western Mediterranean region conceals the interpretation of the evolutionary history of its current fauna, as similar distribution patterns may have very different temporal and geographic origins. Particularly intriguing are some subterranean species in islands, which origin is usually difficult to interpret as their strongly modified morphologies obscure their relationships. We studied subterranean taxa and their likely relatives of two groups of ground beetles in the western Mediterranean: the Duvalius lineage ("isotopic" Trechini) and Molopina (Pterostichini). We included specimens from the islands of Mallorca, Sardinia and Sicily, plus mainland Europe and North Africa. Phylogenetic relationships were reconstructed with a combination of mitochondrial and nuclear data, and divergence dates were estimated with Bayesian methods using the same a priori molecular evolutionary rates for the same gene fragments in the two groups. In the Duvalius lineage, the subgenus Trechopsis, including all the highly modified cave or nivicolous species, was found to be polyphyletic: the species from Mallorca was found to be of Pleistocene origin and sister to the less modified species of subgenus Duvalius from the same island, whereas the Algerian species of Trechopsis were, on the contrary, related to the Sicilian Duvalius, indicating a northern colonisation route during the late Pliocene. Molopina was divided into three main lineages: the genera Abax, Percus, and the Molops groups of genera. The basal diversification of the latter was dated within a temporal window (35–25 Ma) fully congruent with the tectonic opening of the western Mediterranean basin and included six main lineages with uncertain relationships among them: the epigean genera (a) Molops and (b) Tanythrix ; and the subterranean (c) Typhlochoromus (Eastern Alps), (d) Speomolops (Sardinia), (e) Henrotius (Mallorca) and (f) a strongly supported clade including the Pyrenean genera Zariquieya, Oscadytes and Molopidius . Despite the similar distribution of some of their subterranean taxa, the two studied groups show a strongly contrasting origin and mode of diversification. While the Duvalius lineage had a recent origin, with complex colonisation patterns and widespread morphological convergence among the subterranean species, the subterranean Molopina had an ancient vicariant origin resulting from the tectonic opening of the western Mediterranean basin.